Prevalence and associated risk factors of visual impairment in school children: mHealth-based vision screening in government schools of Rawalpindi, Pakistan - Javed, Ayesha; Mohsin, Shamaila; Habib, Ramsha; Malik, Uzma Ahsan; Ahmad, Abdul Momin Rizwan (Frontiers in Medicine, 2025)
BackgroundSchool-based vision screening plays a vital role in identifying visual problems at an early stage. There is limited evidence on the frequency of visual impairment and its associated risk factors among school-aged children.ObjectiveThis research aimed to assess the prevalence of visual impairment and its associated risk factors among school children enrolled in Government Schools of Rawalpindi.MethodologyAn analytical cross-sectional study was conducted among 320 schoolchildren in the Rawalpindi district of Punjab province from July to December 2024. Presenting visual acuity was assessed using the validated Peek Acuity app on smartphone with the tumbling E optotypes. Visual impairment was defined as presenting visual acuity worse than 6/12, based on failure to correctly identify at least four out of five optotypes at the 6/12 level at a testing distance of 3 m. A validated questionnaire was utilized to assess risk factors associated with visual impairment. The prevalence of visual impairment was presented as frequencies and percentages. Binary logistic regression was performed with visual impairment as the dependent variable, considering age, gender, father's educational status, mother's educational status, household income, maternal illness during pregnancy, parent with visual impairment, sibling with visual impairment, birth weight, gestational age, complications at birth, serious infection during childhood, history of head trauma or injury, duration of television exposure, and duration of mobile/computer exposure as independent variables. Variables with a p < 0.05 and a 95% confidence interval in the multivariate model were considered statistically significant.ResultsA total of 320 study participants were included in this study. Visual impairment was identified in 82 children (25.6%), consisting of 35 males (42.68%) and 47 females (57.3%). It was categorized as mild in 30 (36.58%) and moderate in 52 (63.41%) children. In multivariate analysis, parent with visual impairment [4.201 (2.221–7.948)], low birth weight [0.376 (0.189–0.749)], small gestational age [0.231 (0.113–0.475)] and exposure to mobile and computer devices [2.368 (1.040–5.393)] were factors significantly associated with visual impairment.ConclusionThis study identified a high burden of visual impairment among schoolchildren, with a greater proportion observed in females and predominantly presenting with moderate severity.